Unsaturated guluronate oligosaccharide enhances the antibacterial activities of macrophages. Issue 6 (5th March 2014) - Xu, Xu; Bi, Decheng; Wu, Xiaoting; Wang, Qingqing; Wei, Gaobin; Chi, Lianli; Jiang, Zedong; Oda, Tatsuya; Wan, Min
ABSTRACT: Alginate from marine seaweeds is receiving continuous attention owing to its wide physiological activities. Herein, we sought to elucidate possible effects of alginate‐derived polyguluronate (PG) and unsaturated guluronate oligosaccharide (GOS) on antibacterial activities of macrophages. Our results showed that, in contrast to PG, GOS markedly increased the phagocytosis of IgG‐opsonized Escherichia coli and Staphylococcus aureus and further inhibited the survival of intracellular bacteria in macrophages. In line with this, GOS treatment resulted in the enhanced expression of Fcγ receptors on macrophages. In addition, GOS activated NF‐κB pathway, induced TNF‐α secretion, and elevated the expression of inducible nitric oxide synthase and the production of nitric oxide. Meanwhile, GOS stimulated the production of reactive oxygen species in macrophages. Moreover, guluronate trimer to hexamer (G3–G6) in GOS exhibited significant activity that increased the bacterial phagocytosis of macrophages, with the pentamer (G5), displaying the highest activity. Finally, our in vivo results further confirmed that GOS but not PG significantly improved bacterial clearance in murine acute peritonitis. In conclusion, GOS enhances antibacterial activities of macrophages via modulating signaling pathways related to innate immunity, suggesting that GOS might be a promising therapeutic candidate to improve the host defense against bacterial infection. Xu, X., Bi, D., Wu, X., Wang, Q., Wei, G., Chi, L., Jiang, Z., Oda, T., and Wan, M. Unsaturated guluronate oligosaccharide enhances the antibacterial activities of macrophages. FASEB J . 28, 2645–2654 (2014). www.fasebj.org